Pengaruh Kontribusi Efektivitas Pajak Daerah, Retribusi Daerah, Terhadap Kemandirian Keuangan Daerah Pemerintah Kabupaten /Kota Guna Mendukung Otonomi Daerah Provinsi Sumatra Utara Periode 2016-2018 - Desy Riantika Putri (Asosiasi Dosen Akuntansi Indonesia, 2021)
Regional financial independence shows the ability of the regional government to finance government activities, development and services to the people who have paid taxes and levies as sources needed by the region. As regional original income, regional taxes and regional levies are sources of income that are indispensable for increasing regional financial independence. The purpose of this study is to determine the effect of local taxes and regional levies on regional financial independence in North Sumatra Regency in 2016-2018. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, coefficient of determination (R2). The results of this test show that partially the Regional Tax variable has a significant effect on regional financial independence because the Tcount value is 4.857 > Ttable value is 1.98498 with a significance level of 0.004 <0.05. And the regional levy variable, the value of Tcount is 2.960 > the value of Ttable is 1.98498 with a significance level of 0.002 <0.05. And simultaneously Fcount is 12,792 with Ftable value is 3,09. This shows the value of Fcount 12.792 > Ftable 3.09 while the significance level is 0.000 <0.05. with the percentage of variable X (Regional Taxes and Levies) to variable Y (Regional Financial Independence) of 21%. While 79% is influenced by variables not examined by the author.